Unique Habitat for Benthic Foraminifera in Subtidal Blue Holes on Carbonate Platforms - Little, Shawna N.; van Hengstum, Peter J.; Beddows, Patricia A.; Donnelly, Jeffrey P.; Winkler, Tyler S.; Albury, Nancy A. (Frontiers in Ecology and Evolution, 2021)
Dissolution of carbonate platforms, like The Bahamas, throughout Quaternary sea-level oscillations have created mature karst landscapes that can include sinkholes and off-shore blue holes. These karst features are flooded by saline oceanic waters and meteoric-influenced groundwaters, which creates unique groundwater environments and ecosystems. Little is known about the modern benthic meiofauna, like foraminifera, in these environments or how internal hydrographic characteristics of salinity, dissolved oxygen, or pH may influence benthic habitat viability. Here we compare the total benthic foraminiferal distributions in sediment-water interface samples collected from < 2 m water depth on the carbonate tidal flats, and the two subtidal blue holes Freshwater River Blue Hole and Meredith’s Blue Hole, on the leeward margin of Great Abaco Island, The Bahamas. All samples are dominated by miliolid foraminifera (i.e., Quinqueloculina and Triloculina), yet notable differences emerge in the secondary taxa between these two environments that allows identification of two assemblages: a Carbonate Tidal Flats Assemblage (CTFA) vs. a Blue Hole Assemblage (BHA). The CTFA includes abundant common shallow-water lagoon foraminifera (e.g., Peneroplis, Rosalina, Rotorbis), while the BHA has higher proportions of foraminifera that are elsewhere known to tolerate stressful environmental conditions of brackish and dysoxic waters elsewhere (e.g., Pseudoeponides, Cribroelphidium, Ammonia). We also observe how the hydrographic differences between subtidal blue holes can promote different benthic habitats for foraminifera, and this is observed through differences in both agglutinated and hyaline fauna. The unique hydrographic conditions in subtidal blue holes make them great laboratories for assessing the response of benthic foraminiferal communities to extreme environmental conditions (e.g., low pH, dysoxia).